Axial mechanical and structural characterization of keratoconus corneas. (October 2018) - Mikula, Eric; Winkler, Moritz; Juhasz, Tibor; Brown, Donald J.; Shoa, Golroxan; Tran, Stephanie; Kenney, M. Cristina; Jester, James V.
Abstract: Purpose: Previous studies indicate that there is an axial gradient of collagen lamellar branching and anastomosing leading to regional differences in corneal tissue stiffness that may control corneal shape. To further test this hypothesis we have measured the axial material stiffness and quantified the collagen lamellar complexity in ectatic and mechanically weakened keratoconus corneas (KC). Methods: Acoustic radiation force elastic microscopy (ARFEM) was used to probe the axial mechanical properties of the cone region of three donor KC buttons. 3 Dimensional second harmonic generation microscopy (3D-SHG) was used to qualitatively evaluate lamellar organization in 3 kC buttons and quantitatively measure lamellar branching point density (BPD) in a separate KC button that had been treated with epikeratophakia (Epi-KP). Results: The mean elastic modulus for the KC corneas was 1.67 ± 0.44 kPa anteriorly and 0.970 ± 0.30 kPa posteriorly, substantially below that previously measured for normal human cornea. 3D-SHG of KC buttons showed a simplified collagen lamellar structure lacking noticeable angled lamellae in the region of the cone. BPD in the anterior, posterior, central and paracentral regions of the KC cornea were significantly lower than in the overlying Epi-KP lenticule. Additionally, BPD in the cone region was significantly lower than the adjacent paracentral region in the KC button. Conclusions: The KC cornea exhibits an axial gradient of mechanical stiffness and a BPD that appears substantially lower in the cone region compared to normal cornea. The findings reinforce the hypothesis that collagen architecture may control corneal mechanical stiffness and hence corneal shape. Highlights: The anterior is stiffer than the posterior in the keratoconus cornea cone. The keratoconus cornea cone is significantly less stiff than the healthy cornea. Collagen complexity in the anterior keratoconus cone is greater than the posterior. Collagen complexity in the keratoconus cone is less than in the healthy cornea. Collagen complexity outside of the keratoconus cone is greater than within.